2016
DOI: 10.1016/j.vetmic.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological survey of enteric viruses in wild boars in the Czech Republic: First evidence of close relationship between wild boar and human rotavirus A strains

Abstract: Population of wild boar is increasing in the whole Europe, the animals migrate close to human habitats which greatly increases the possibility of natural transmission between domestic animals or humans and wild boars. The aim of the study was to estimate in population of free-living wild boar in the Czech Republic the prevalence of enteric viral pathogens, namely rotavirus groups A and C (RVA and RVC), porcine reproductive and respiratory syndrome virus (PRRSV), and members of family Coronaviridae (transmissib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…EV-Gs are endemic among the Japanese pig population [20]. The EV-G detection rate of 37.5 % (30/80) in Japanese wild boars is lower than the 50 % (5/10 free-living wild boars) in Hungary [33] and 69.4 % (50/72 domestic boars) in Czech Republic [34], but higher than the 8.9 % (4/45 domestic boars) in Vietnam [6] and 2.5 % (5/203 free-ranging wild boars) in the Czech Republic [35]. In this study, EV-Gs were predominantly detected from juvenile wild boars, suggesting that juveniles may be more susceptible to EV-G.…”
Section: Discussionmentioning
confidence: 99%
“…EV-Gs are endemic among the Japanese pig population [20]. The EV-G detection rate of 37.5 % (30/80) in Japanese wild boars is lower than the 50 % (5/10 free-living wild boars) in Hungary [33] and 69.4 % (50/72 domestic boars) in Czech Republic [34], but higher than the 8.9 % (4/45 domestic boars) in Vietnam [6] and 2.5 % (5/203 free-ranging wild boars) in the Czech Republic [35]. In this study, EV-Gs were predominantly detected from juvenile wild boars, suggesting that juveniles may be more susceptible to EV-G.…”
Section: Discussionmentioning
confidence: 99%
“…Some genotypes and genotype combinations detected in foxes indicate a common origin and possible interspecies transmission events involving RVA strains considered to be of porcine (G9P [23], G11P [13]) and bovine/Artiodactyla (G8P [14], G10P [11]) origin [7,18]. Some of these genotypes have already been detected in wildlife, for instance, the RVA G9, G11, P [13] and P [23] genotypes in wild boars [19,24]. Since foxes can surely come in contact with both domestic and wild animals and their excrements, the exact origin of interspecies transmission cannot be defined on the basis of sequence analysis only.…”
Section: Discussionmentioning
confidence: 96%
“…Since this is the first study of RVA prevalence in red fox population, we are unable to put our results in a wider context and directly compare our results with those of other authors. However, studies on other wildlife species in a similar environment, which resorted to a similar methodological approach, indicated a considerably lower RVA prevalence in wild boars [19] and roe deer [20]. Moreover, the study on roe deer applied the same broad-range VP2 real-time RT-PCR designed for one of the most conserved regions of the RVA genome and tested on various human and animal samples [21].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that several of these CoVs can remain infectious on animal feed for extended periods of time (up to 42 days for PDCoV and TGEV, and 7 days for PEDV; ( Trudeau et al, 2017 ), suggesting that these CoVs could increase their chance of spillover with high environmental persistence. There is also one pig beta-CoV, the CoV genus that SARS-CoV and SARS CoV-2 belong to, that is highly prevalent in domestic swine and is named porcine hemagglutinating encephalomyelitis virus (PHEV) ( Mora-Diaz et al, 2019 ; Wang et al, 2019 ), but it has not been detected in wild pigs ( Moutelikova et al, 2016 ) (although surveillance has been minimal). In summary, CoVs from other host species are highly available for spillover into pigs, where the virus can successfully replicate.…”
Section: Why Might Pigs Contribute To Emergence Of Zoonotic Covs?mentioning
confidence: 99%